Point-contact Andreev-reflection spectroscopy of doped manganites: Charge carrier spin-polarization and proximity effects (Review Article) - Krivoruchko, V.N.; D’yachenko, A.I.; Tarenkov, V.Yu. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Materials with spin-polarized charge carriers are the most demanded in the spin-electronics. Particularly requested are the so-called half-metals which have the maximum attainable value of carrier spin polarization. Doped manganites are in the list of compounds with, potentially, half-metallic properties. The point-contact (PC) Andreevreflection (AR) spectroscopy is a robust and direct method to measure the degree of current spin polarization. In this report, advances in PCAR spectroscopy of ferromagnetic manganites are reviewed. The experimental results obtained on “classic” s-wave superconductor — ferromagnetic manganites PCs, as well as related theoretical models applied to deduce the actual value of charge carrier spin-polarization, are discussed. Data obtained on “proximity affected” contacts is also outlined. Systematic and repeatable nature of a number of principal experimental facts detected in the AR spectrum of proximity affected contacts suggests that some new physical phenomena have been documented here. Different models of current flow through a superconductor–half-metal ferromagnet interface, as well as possibility of unconventional superconducting proximity effect, have been discussed.